Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÑÐºÑÑ‚Ñ€Ð°ÐºÑ‚Ð¾Ð² Ð³Ð¾Ð»Ð¾Ð²Ð½Ð¾Ð³Ð¾ Ð¼Ð¾Ð·Ð³Ð° Ð¸ Ð¿ÐµÑ‡ÐµÐ½Ð¸ Ð½Ð° ÑÑ„Ñ„ÐµÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚ÑŒ Ð³Ð¸Ð¿Ð¾Ñ‚ÐµÑ€Ð¼Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ Ñ…Ñ€Ð°Ð½ÐµÐ½Ð¸Ñ Ð¸Ð·Ð¾Ð»Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… Ð½ÐµÑ€Ð²Ð½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº Ð½Ð¾Ð²Ð¾Ñ€Ð¾Ð¶Ð´ÐµÐ½Ð½Ñ‹Ñ… ÐºÑ€Ñ‹Ñ - Shevchenko, Mariya V.; Sukach, Aleksandr N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
The behavior of isolated neural cells of newborn rats in culture after hypothermic storage in sucrose-based solution and saline medium DMEM/F-12 in the presence of serum or brain and liver extracts was studied. Hypothermic storage in saline medium DMEM/F-12 in the presence of serum or liver and brain extracts and sucrose-based solution without serum or in the presence of brain extract allows to preserve the differentiated and stem/progenitor cells populations for 2 days. The hypothermic storage of cells for more than this period results in their death. During the hypothermic storage in DMEM/F-12 the brain/liver extracts together with the serum augment the survival rate for newborn rats neural cells, and under hypothermic storage in sucrose-based solution the brain and liver extracts cause positive and negative effects, respectively, on neural cell survival. It was found that the brain and liver extracts allow to effectively substitute the serum during the hypothermic storage of neural cells in DMEM/F-12 medium.Probl Cryobiol Cryomed 2015; 25(1): 13-23.